2015
DOI: 10.1038/mtm.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effects of ectopic gp91phox expression in XCGD iPSC-derived neutrophils

Abstract: For the treatment of monogenetic hematological disorders, restoration of transgene expression in affected cell populations is generally considered to have beneficial effects. However, X-linked chronic granulomatous disease (XCGD) is unique since the appearance of functional neutrophils in the peripheral blood following hematopoietic stem cell gene therapy is transient only. One contributing factor could be the occurrence of detrimental effects secondary to ectopic gp91phox expression in neutrophils, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Some of the hiPSC lines established in this study are already being used for disease studies by our collaborators and our research team, and the results will be reported elsewhere in the near future. For example, we have confirmed that neutrophilic cells differentiated from the TkSCG3 and TkSCG4 lines, derived from X-CGD patients, show severe defects in reactive oxygen species production (data not shown), similar to another X-CGD-iPSC line that we reported previously [39]. Such findings indicate the applicability of the established hiPSC lines to disease-modeling studies.…”
Section: Discussionsupporting
confidence: 87%
“…Some of the hiPSC lines established in this study are already being used for disease studies by our collaborators and our research team, and the results will be reported elsewhere in the near future. For example, we have confirmed that neutrophilic cells differentiated from the TkSCG3 and TkSCG4 lines, derived from X-CGD patients, show severe defects in reactive oxygen species production (data not shown), similar to another X-CGD-iPSC line that we reported previously [39]. Such findings indicate the applicability of the established hiPSC lines to disease-modeling studies.…”
Section: Discussionsupporting
confidence: 87%
“…Peripheral blood samples were obtained from a patient with PFE (38-y-old woman) with a nucleotide substitution of 395C>T in the PTH1R gene and a healthy volunteer upon informed consent following the Declaration of Helsinki standard ethics procedure. We generated iPSCs according to previously reported procedures (Lin et al 2015; Kubara et al 2018), with some modifications. Yamanaka factors were introduced into CD34 + hematopoietic stem/progenitor cells isolated from a peripheral blood sample with a Sendai virus SeVdp vector (KOSM302L; Nishimura et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…However, allogeneic transplants are complicated by graft-versus-host disease and limited donor availability (1). Gene therapy using autologous HSPCs modified by integrating viral vectors has provided clinical benefit but is complicated by vectorrelated genotoxicities and transgene expression driven by exogenous promoters (2)(3)(4). Recent lentiviral vector gene therapy trials have reported clinical benefits without any insertional mutagenesis (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%